Application of Geolocation Methods in Student Attendance System Design - Yoga Rizya Pratama; Apri Siswanto (Data Science Insights, 2024)
Universitas Islam Riau is one of the universities in Riau province that is of interest to high school graduate students as a place to continue their studies at a higher level. Implementing the student attendance process at the Universitas Islam Riau is still done manually; this causes less efficiency and effectiveness of attendance activities, starting from data collection, processing presence data, and storing and searching processes, which take time. In some cases, fraud may occur, such as falsifying the presence of someone represented by another party. Then, we need a system that can record the attendance of students whose positions are within the scope of the class radius. Geolocation can capture device coordinates by utilizing latitude and longitude, which will be used to measure the distance between classes and students. If the student's position is outside the class radius determined by each lecturer, then the student cannot fill in attendance. If the student's position is within the scope of the class radius that has been determined, students can fill in attendance. In the research, we succeeded in designing a student attendance system based on the geolocation method. Security to overcome fake GPS managed to function properly, and fingerprints to take attendance can work properly. From the results of Black box testing, the system can run well and is free from syntax and functional errors.